Identification of Compounds Released During Pyrolysis of Palm Kernel Shell (PKS) Using Pyrolysis-GC/MS - Dieni Mansur; Sabar Pangihutan Simanungkalit (Dept. of Chemical Engineering, Diponegoro University, 2017)
Pyrolysis is one of thermochemical conversion to convert biomass into bio-oil. The higher energy content in bio-oil suggests its potential as a raw material in the production of energy, bio-fuels, and other chemicals. Pyrolysis of PKS and the chemicals released were studied using pyrolysis–gas chromatography/mass spectrometry (Py-GC/MS) at 400-600°C. Prior to pyrolysis, thermogravimetry experiments were carried out to monitor the degradation temperature of hemicellulose, cellulose, and lignin in the PKS. Degradation of hemicellulose occurred within a temperature range of 150-330°C, whereas the cellulose was degraded in temperatures range between 330-400°C. Degradation of lignin took place within a broad range of temperatures, which reached maximum at temperatures range of 200-500°C. Based on the Py-GC/MS results, pyrolysis of PKS at 400°C produced bio-oil that can be used as biofuel due to its high aromatic compounds but low carboxylic acids contents. Keywords: bio-oil; chemical; palm kernel shell; Py-GC/MS; thermogravimetry .